Mapping Texture Phase Diagram of Artificial Haptic Stimuli Generated by Vibrotactile Actuators - Dharma, Anak Agung Gede; Tomimatsu, Kiyoshi (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
We propose a classification method of tactile sensations elicited by artificial haptic stimuli by using Japanese onomatopoeias/adjectives. This method classifies adjectives based on user subjective perception and plot basic components of artificial haptic stimuli. The comparison of perceived tactile sensations from artificial haptic stimuli and genuine physical materials is also discussed in this paper.